Amazon aquatic biodiversity imperiled by oil spills - Azevedo-Santos, Valter M. [UNESP]; Garcia-Ayala, James R. [UNESP]; Fearnside, Philip M.; Esteves, Francisco A.; Pelicice, Fernando M.; Laurance, William F.; Benine, Ricardo C. [UNESP] (Springer, 2016)
Oil exploitation poses a significant threat to freshwater biodiversity, and future plans to develop petroleum leases in the Amazon Basin should be seem with caution. A series of oil spills have significantly affected biodiversity and human activities in some Amazonian basins, indicating that disturbances by petroleum activities will increase in the region, particularly in upper basins and river headwaters. Measures are needed to reduce the risk of spills and to minimize their impacts. More fundamentally, changes in decision making are needed that give proper weight to these impacts.
Keywords: Petroleum; Pollution; Fish kill; Environmental impact; Freshwater; Development policy